Transcriptome Analyses Reveal the Involvement of Both C and N Termini of Cryptochrome 1 in Its Regulation of Phytohormone-Responsive Gene Expression in Arabidopsis - Wang, Wen-Xiu; Lian, Hong-Li; Zhang, Li-Da; Mao, Zhi-Lei; Li, Xiao-Ming; Xu, Feng; Li, Ling; Yang, Hong-Quan (Frontiers in Plant Science, 2016)
Cryptochromes (CRY) are blue-light photoreceptors that mediate various light responses in plants and animals. It has long been demonstrated that Arabidopsis CRY (CRY1 and CRY2) C termini (CCT1 and CCT2) mediate light signaling through direct interaction with COP1. Most recently, CRY1 N terminus (CNT1) has been found to be involved in CRY1 signaling independent of CCT1, and implicated in the inhibition of gibberellin acids (GA)/brassinosteroids (BR)/auxin-responsive gene expression. Here, we performed RNA-Seq assay using transgenic plants expressing CCT1 fused to β-glucuronidase (GUS-CCT1, abbreviated as CCT1), which exhibit a constitutively photomorphogenic phenotype, and compared the results with those obtained previously from cry1cry2 mutant and the transgenic plants expressing CNT1 fused to nuclear localization signal sequence (NLS)-tagged YFP (CNT1-NLS-YFP, abbreviated as CNT1), which display enhanced responsiveness to blue light. We found that 2,903 (67.85％) of the CRY-regulated genes are regulated by CCT1 and that 1,095 of these CCT1-regulated genes are also regulated by CNT1. After annotating the gene functions, we found that CCT1 is involved in mediating CRY1 regulation of phytohormone-responsive genes, like CNT1, and that about half of the up-regulated genes by GA/BR/auxin are down-regulated by CCT1 and CNT1, consistent with the antagonistic role for CRY1 and these phytohormones in regulating hypocotyl elongation. Physiological studies showed that both CCT1 and CNT1 are likely involved in mediating CRY1 reduction of seedlings sensitivity to GA under blue light. Furthermore, protein expression studies demonstrate that the inhibition of GA promotion of HY5 degradation by CRY1 is likely mediated by CCT1, but not by CNT1. These results give genome-wide transcriptome information concerning the signaling mechanism of CRY1, unraveling possible involvement of its C and N termini in its regulation of response of GA and likely other phytohormones.